HUBUNGAN KEBERADAAN JENTIK Aedes aegypti DAN PELAKSANAAN 3M PLUS DENGAN KEJADIAN PENYAKIT DBD DI LINGKUNGAN XVIII KELURAHAN BINJAI KOTA MEDAN TAHUN 2012 - Sulina Parida S; Surya Dharma; Wirsal Hasan (Lingkungan dan Kesehatan Kerja, 2013)
The relation of Aedes aegypti larva existence and 3M Plus implementation with DHF disease in Area XVIII Binjai District Medan. Medan is one of DHF endemic area and the most endemic subdistrict is Medan Denai Subdistrict. The most effective way to eradicate DHF disease is with eradicating mosquito nest or PSN DBD, so that is important to know the Aedes aegypti larva existence and effectiveness of 3M Plus implementation.This research aims to know the relation of Aedes aegypti larva existence and 3M Plus implementation with DHF disease. The research location is in Area XVIII Binjai District Medan Denai Subdistrict. This research samples are 100 housewive, that is taken by purposive sampling technique. This research is analytic survey with cross sectional design study using Exact Fisher test.Results showed that the House Index value is 5%, Container Index is 4%. 3M Plus implementation that includes to good category 78% and bad 22% . The relation of Aedes aegypti larva existence with DHF disease has p=0,002. The relation of 3M Plus implementation with DHF disease has p=0,047. From the results, it can be known that there is relation of Aedes aegypti larva existence and 3M Plus implementation with DHF disease in Area XVIII Binjai District. It is suggested to Medan Health Department and Desa Binjai Health Service Center to socialize to do eradicating Aedes aegypti mosquito nest or PSN DBD regularly to decrease the number of DHF disease in Binjai District especially in Area XVIII. Keywords : Larva Existence, 3M Plus, DHF